An Item Response Theory (IRT) approach using Nested Logit Model (NLM) in analyzing the number series items of the Philippine Aptitude Classification Test (PACT) - Lantano, Armi S.
Abstract (Although the use of unidimensional Item Response Theory (IRT) in analysing responses to multiple choice items has been widespread, its application is mostly based on dichotomously scored data. By collapsing responses to multiple choice items into either correct or incorrect only, analysis on how each incorrect option performs in relation to student ability is not possible. Likewise, the use of polytomous IRT models for unordered responsees (e.g. multiple choice items) such as the Nominal Response Model may alter the statistical form of the correct response and thus, results to decrease in precision. Hence, Suh and Bolt (2010) proposed the Nested Logit Model (NLM), a new modelling approach which has established its consistency as to how the correct response is modelling approach which has established its consistency as to how the correct response is modelled, whether incorporating or not the distracter information. They further contented that this better approximates the strategy of arriving at a correct answer following a sequential process such as problem solving precedes guessing. This study, therefore, explores the use of NLM in analysing the Number Series items of the Philippine Aptitude Classification Test (PACT) to improve the quality of items by detecting problematic distracters and to increase the precision to estimates ability of students by including/considering distracter selection using a total of 1,620 second year high school students who participated in the pilot administration conducted by the Center for Educational Measurement, Inc. (CEM) in July-August 2012. Results of the study showed that the Number Series Items could still be improved and that attending to the distracters in scoring would yield slight but significant increase in precision at the low to moderate ability estimates. This study, therefore, suggests possible redesigning approaches for the Number Series items and further analysis of the other subtests of the PACT using the NLM for better measurement accuracy and discrimination among students).
June 2017
Thesis (M.S. Statistics)--University of the Philippines, Diliman.
Keywords: Econometrics; Philippine Aptitude Classification Test (PACT)